Accelerated Greenland Ice Sheet Mass Loss Under High Greenhouse Gas Forcing as Simulated by the Coupled CESM2.1-CISM2.1 - Muntjewerf, L. (author); Sellevold, R. (author); Vizcaino, M. (author); Ernani da Silva, C. (author); Petrini, M. (author); Thayer-Calder, Katherine (author); Scherrenberg, Meike D.W. (author); Bradley, S.L. (author); Katsman, C.A. (author); Fyke, Jeremy (author); Lipscomb, William H. (author); Lofverstrom, Marcus (author); et al. (Journal of Advances in Modeling Earth Systems, 2020)
The Greenland ice sheet (GrIS) is now losing mass at a rate of 0.7 mm of sea level rise (SLR) per year. Here we explore future GrIS evolution and interactions with global and regional climate under high greenhouse gas forcing with the Community Earth System Model version 2.1 (CESM2.1), which includes an interactive ice sheet component (the Community Ice Sheet Model v2.1 [CISM2.1]) and an advanced energy balance-based calculation of surface melt. We run an idealized 350-year scenario in which atmospheric CO 2 concentration increases by 1% annually until reaching four times pre-industrial values at year 140, after which it is held fixed. The global mean temperature increases by 5.2 and 8.5 K by years 131–150 and 331–350, respectively. The projected GrIS contribution to global mean SLR is 107 mm by year 150 and 1,140 mm by year 350. The rate of SLR increases from 2 mm yr −1 at year 150 to almost 7 mm yr −1 by year 350. The accelerated mass loss is caused by rapidly increasing surface melt as the ablation area expands, with associated albedo feedback and increased sensible and latent heat fluxes. This acceleration occurs for a global warming of approximately 4.2 K with respect to pre-industrial and is in part explained by the quasi-parabolic shape of the ice sheet, which favors rapid expansion of the ablation area as it approaches the interior “plateau.”. Physical and Space Geodesy Environmental Fluid Mechanics